Do attraction, accesibility, amenities and ancillary for interest visiting of visitor? the role of customers satisfaction - Ambarwati, Diana; Munawaroh, Nuril Aulia (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of attractiveness, accessibility, amenities and ancillaries on visit interest through customer satisfaction and add experience for researchers in applying research variables. This research employs a quantitative methodology. Using a purposive sample technique, the population and sample for this study consisted of 33 visitors to Kampung Tani, Jamsaren, Kediri City, who came between July and August of 2023. According to the study's findings, factors like attraction, accessibility, amenities, and ancillary services had no discernible positive impact on tourists' desire to visit. Visitor satisfaction is not directly and significantly positively impacted by the factors of attraction, accessibility, and amenities. On visitor satisfaction, however, the ancillary variable has a direct and noteworthy positive impact. The impact of the attraction, accessibility, and amenities cannot be mitigated by the positive, negligible variable of visitor satisfaction. The positive, insignificant variable of visitor satisfaction cannot mediate the influence of the attraction, accessibility, amenities and ancillary variables indirectly on the variable of interest in visiting Kampung Tani, Jamsaren, Kediri City.